Posttreatment National Institutes of Health Stroke Scale Is Superior to the Initial Score or Thrombolysis in Cerebral Ischemia for 3-Month Outcome. Issue 4 (April 2018) - Jeong, Han-Gil; Kim, Beom Joon; Choi, Jay Chol; Hong, Keun-Sik; Yang, Mi Hwa; Jung, Cheolkyu; Han, Moon-Ku; Bae, Hee-Joon
Abstract : Background and Purpose—: The majority of ischemic stroke patients receiving endovascular recanalization therapy (EVT) experience variable changes of neurological severities during the hyperacute period. We hypothesized that the National Institutes of Health Stroke Scale (NIHSS) score after EVT is a better prognostic factor compared with the initial NIHSS score or revascularization status. Methods—: We identified 566 stroke patients who received EVT at Seoul National University Bundang Hospital between April 2008 and December 2015. We prospectively collected post-EVT NIHSS score, which was measured in the angiography suite by on-duty physicians after completion of EVT. Model 1 included baseline predictors including an initial NIHSS score. In model 2, 3, and 4, revascularization status, post-EVT NIHSS score, or both were additionally included. The discrimination powers for modified Rankin Scale score of 0 to 2 at 3 months were assessed using C statistic, integrated discrimination index, and category-free net reclassification index. Results—: The median of initial and post-EVT NIHSS score were 14 (9–19) and 11 (5–17) points, respectively (an improvement, 58.8%; no change, 20.7%; deterioration, 20.5%). A modified Rankin Scale score 0 to 2 at 3 months was achieved in 47%. Based on the results of differences among the C statistics, both model 3 and model 4 (C statistics: 0.896 and 0.906) showed significantly increased discrimination power for modified Rankin Scale score 0 to 2 at 3 months than the model 1 or 2 (C statistics: 0.802 and 0.834, P values<0.001 for all comparisons). Model 4 showed significant improvement of both integrated discrimination index and net reclassification index as compared with all other models, but the magnitude of improvement from model 3 to model 4 (integrated discrimination index, 0.021; net reclassification index, 0.322) was modest. Conclusions—: Incorporation of post-EVT NIHSS score conferred better discrimination power to the statistical models for functional recovery. Post-EVT NIHSS score may be an appropriate baseline factor when evaluating an intervention after hyperacute period. Abstract : Supplemental Digital Content is available in the text.